(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
Crime is not a random event. Certain lifestyles increase the risk of victimization, and psychological, social, and economic factors are associated with criminal involvement. Crime varies over time: it is more common in the evening than in the morning, on weekends more than on weekdays, and in the summer more than in the winter. Crime mapping is the process by which crime analysts and researchers use location information about criminal events to discover spatial patterns in criminal activity.(Boba, 2005) In the past, crime mapping efforts typically involved placing physical markers, such as pins, on maps to indicate the locations where crimes occurred. Patterns of criminal activity were determined primarily through visual inspection of these maps. Researchers and crime analysts can then use a variety of analytical software packages to examine and discover patterns of criminal activity from these virtual maps. This paper explores the concepts, theoretical approaches, and key findings related to crime mapping, with an emphasis on its application in crime prevention and suppression strategies. Keywords: Crimes, Criminal information, Clues, Criminal records, Crime mapping, GIS